Proposed Business Strategy for Hoodjabie Wear - Rashyida Amyra Razali; Sobirov Bobur Baxtishodovich (International Journal on Economics, Finance and Sustainable Development, 2022)
The changing lifestyle of Muslim ladies nowadays requires a kind of clothing that fits their active lifestyle, especially when traveling and going on a holiday. However, they must bring many clothes such as long-sleeved clothing and long scarves to suit their attire that complies with the Syariah. Hoodies are becoming a typical style for them due to their simplicity. Therefore, the new inventive dress for Muslim ladies is designed and named Hoodjabie Wear. This new attire is appropriate for Muslim ladies’ daily activities and traveling. I want to address the problem that the hijab will be out of place after a while. Therefore, I want to consider how we can provide women with the options they deserve – hijabs that they can wear easily and travel freely, securely, comfortably, and beautifully. When people travel, especially overseas, they tend to wear a hoodie because it is comfortable and gets cold when riding the plane. For women, specifically, those who wear hijabs, wearing a hoodie sometimes will crumple their hijab or scarf every time they use the hood over their head.